Epigenetic silencing of miR-335 induces migration by targeting insulin-like growth factor-1 receptor in multiple myeloma. Issue 13 (10th November 2019) - Qi, Jing; Shi, Lin-Ying; Wu, Yin; Shen, Xian-Juan; Yuan, Jie; Jin, Chun-Jing; Cong, Hui; Ju, Shao-Qing
Abstract: Multiple myeloma (MM) is a common hematological malignancy and remains incurable. MiRNA-335 is a classic tumor suppressor, yet its expression pattern and biological role in MM is unclear. The aim of the present study was to determine the expression pattern, biological role, and mechanism of miR-335 in MM. In this study, we found that miR-335 expression was decreased in MM. The promoter of miR-335 was also hypermethylated in MM. It was found that over-expression of miR-335 or 5-azacytidine treatment suppressed migration of MM cells and down-regulated the expression of IGF-1R. MiR-335 thus acts as a metastatic suppressor by targeting IGF-1R in MM. Moreover, aberrant promoter hyper-methylation is critical for miR-335 silencing in MM. We also found that miR-335 assisted in predicting both the prognosis and progression of disease in MM patients. Observations might offer a new complementary diagnostic and therapeutic target in MM.